Evaluation of psychological well-being and social impact of atrophic acne scarring: A multinational, mixed-methods studyCapsule Summary - Jerry Tan, MD; Stefan Beissert, MD; Fran Cook-Bolden, MD; Rajeev Chavda, MD; Julie Harper, MD; Adelaide Hebert, MD; Edward Lain, MD, MBA; Alison Layton, MD, PhD; Marco Rocha, MD, PhD; Jonathan Weiss, MD; Brigitte Dréno, MD, PhD (Elsevier, 2022)
Background: Most people with acne are at risk of developing acne scars, but the impact of these scars on patients' quality of life is poorly researched. Objective: To assess the perspective of patients with acne scars and the impact of these scars on their emotional well-being and social functioning. Methods: A 60-minute interview of 30 adults with acne scars informed and contextualized the development of a cross-sectional survey of 723 adults with atrophic acne scars. Results: The main themes identified in the qualitative interviews included acceptability to self and others, social functioning, and emotional well-being. In the cross-sectional survey, 31.6%, 49.6%, and 18.8% of the participants had mild, moderate, and severe/very severe acne scarring. The survey revealed that 25.7% of the participants felt less attractive, 27.5% were embarrassed or self-conscious because of their scars, 8.3% reported being verbally and/or physically abused because of their scars on a regular basis, and 15.9% felt that they were unfairly dismissed from work. In addition, 37.5% of the participants believed that their scars affected people's perceptions about them, and 19.7% of the participants were very bothered about hiding their scars daily. Moreover, 35.5% of the participants avoided public appearances, and 43.2% felt that their scars had negatively impacted their relationships. Limitations: The temporal evaluation of the impact was not estimated. Conclusion: Even mild atrophic acne scarring can evoke substantial emotional, social, and functional concerns.